Students' psychological well-being and its multilevel relationship with immigrant background, gender, socioeconomic status, achievement, and class size. Issue 2 (2nd April 2020) - Alivernini, Fabio; Cavicchiolo, Elisa; Manganelli, Sara; Chirico, Andrea; Lucidi, Fabio
ABSTRACT: School situations trigger affective states that influence students' achievement and well-being. In the present study, we investigated, on the basis of a sample of 26, 470 high-school students and 1, 472 classrooms, the relationship of individual characteristics (immigrant background, gender, socioeconomic status, and achievement) as well as classroom characteristics (group composition and size) with students' feelings at school. The results showed that females, low achievers, immigrants, and low-SES students are more at risk of psychological distress at school, with gender and achievement being the most important factors. A doubly latent model analysis revealed that whereas individual socioeconomic status and achievement have a positive impact on students' feelings, the effect of the two variables at the classroom level is negative. The impact of immigrant classroom composition seems to be limited to positive affect and dependent on students' immigrant generation. Finally, students in smaller classrooms show more psychological well-being at school.